2014
DOI: 10.1136/heartjnl-2014-305697
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure risk prediction in the Multi-Ethnic Study of Atherosclerosis

Abstract: Objective Heart failure (HF) is a leading cause of mortality especially in older populations. Early detection of high-risk individuals is imperative for primary prevention. The purpose of this study was to develop a HF risk model from a population without clinical cardiac disease. Methods The Multi-Ethnic Study of Atherosclerosis is a multicentre observational cohort study following 6814 subjects (mean age 62±10 years; 47% men) who were free of clinical cardiovascular disease at baseline. Median follow-up wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 26 publications
1
80
0
Order By: Relevance
“…The performance of the RF-20 model for incident CHF prediction was better than the MESA-HF 15 risk score (C-index: 0·80, BS: 0·038) with a higher C-index and lower BS.…”
Section: Resultsmentioning
confidence: 84%
“…The performance of the RF-20 model for incident CHF prediction was better than the MESA-HF 15 risk score (C-index: 0·80, BS: 0·038) with a higher C-index and lower BS.…”
Section: Resultsmentioning
confidence: 84%
“…41,42 Diagnoses of probable HF required symptoms, diagnosis by a physician and HF medication use. Symptoms were defined as the presence of shortness of breath or lower extremity swelling.…”
Section: Methodsmentioning
confidence: 99%
“…Such a group are patients with features of asymptomatic left ventricular abnormalities (Stage B Heart Failure). Previous work from our unit and others have shown that, while limitations exist, natriuretic peptide (NP) is an effective screening tool to identify this population (Vasan et al, 2002, Murtagh et al, 2012, Lubien et al, 2002, Nadir et al, 2015, Chahal et al, 2015, Hebert et al, 2010. In addition, risk stratification with NP can facilitate strategies guided by NP, which have been shown to be effective in reducing new onset heart failure and other cardiovascular (CV) events , Huelsmann et al, 2013.…”
Section: Introductionmentioning
confidence: 99%